Reimagining Australian Nationhood: From Young Colony to Ancient Continent (NEW: Emerging scholars in Australian Indigenous Studies, 2019)
Throughout its short history, colonial Australia has suffered from a severe anxiety surrounding its national identity. This essay argues that in limiting its selfhood to the virtues of its British settlers rather than foregrounding the customs of its Indigenous peoples, Australia is simply prolonging its crisis of identity.KeywordsAustralian national identity; settler colonialism; history wars; constitutional recognition